The development, validity, reliability, and norm of a preschool auditory processing assessment scale in China. (September 2022) - Liu, Panting; Lin, Huanxi; Xiao, Zhenglu; Zhu, Huiqin; Ji, Hui; Yao, Mengmeng; Qian, Jun; Tong, MeiLing; Chi, Xia; Hong, Qin
Abstract: Background: Children with auditory processing deficits may face problems with language, learning, and social communication. Aims: To develop a Chinese auditory processing assessment scale for preschool children and establish the norms of the scale. Methods and procedures: The predictive version of the scale was formed by a literature review, qualitative interviews, expert consultation, and a pre-test with a small sample. Nine kindergartens in Nanjing were selected by a stratified cluster sampling plan. First, 734 children from two kindergartens were selected for the large sample pre-test of the scale. Then, 1526 children from four kindergartens and 1151 children from three kindergartens were selected for the reliability and validity analysis and confirmatory factor analysis, respectively. The standardized norm data of the scale were established based on the 3411 points of scale data of the nine kindergartens. Finally, the clinical usefulness of the scale was analyzed by comparing the results of objective auditory processing tests in children with normal and abnormal auditory processing prompted by the score on the scale. Outcomes and results: The preschool auditory processing assessment scale includes 5 dimensions and 30 items. The Cronbach's alpha value of the scale is greater than 0.9. The confirmatory factor analysis results verify that the scale structure is reasonable. The percentile norm of the scale was established. The results of electrophysiological tests of the normal and abnormal auditory processing groups were statistically different ( P  < 0.05). Conclusions and implications: The developed preschool auditory processing assessment scale has good reliability and validity. The scale is suitable for clinical application. Highlights: The scale has good reliability and validity. The standardized data of the preschool auditory processing assessment scale were established. The scale has good clinical application value.